Are narcissists always bad apples? The relationship between employee narcissism and creative deviance - Zhang, Kaixin; Cui, Zilong (Frontiers in Psychology, 2022)
The purpose of this study is to explore the effect of employee narcissism on creative deviance through creative self-efficacy and the moderation of this effect through transformational leadership. Research data were collected using a three-wave lagged model (n=446) from 446 employees of 6 Chinese firms to examine the hypothesized moderated mediation model. The findings show that narcissism was positively related to creative deviance and that creative self-efficacy partially mediated that relationship. Transformational leadership strengthens the effect of narcissism on creative self-efficacy, and there is a positive indirect relationship between employee narcissism and creative deviance through creative self-efficacy when transformational leadership is high. These results deepen our theoretical understanding of the antecedents of creative deviance by demonstrating the positive associations between employee narcissism and creative deviance. The current study also contributes to the literature by identifying the mediating role of creative self-efficacy and the moderating role of transformational leadership to explain the relationship between employee narcissism and creative deviance.